Stimulatory G-Protein α Subunit Modulates Endothelial Cell Permeability Through Regulation of Plasmalemma Vesicle-Associated Protein - He, Lifan; Lu, Hanlin; Ji, Xuyang; Chu, Jianying; Qin, Xiaoteng; Chen, Min; Weinstein, Lee S.; Gao, Jiangang; Yang, Jianmin; Zhang, Qunye; Zhang, Cheng; Zhang, Wencheng (Frontiers in Pharmacology, 2022)
Endothelial cell leakage occurs in several diseases. Intracellular junctions and transcellular fashion are involved. The definite regulatory mechanism is complicated and not fully elucidated. The alpha subunit of the heterotrimeric G-stimulatory protein (Gsα) mediates receptor-stimulated production of cyclic adenosine monophosphate (cAMP). However, the role of Gsα in the endothelial barrier remains unclear. In this study, mice with knockout of endothelial-specific Gsα (GsαECKO) were generated by crossbreeding Gsαflox/flox mice with Cdh5-CreERT2 transgenic mice, induced in adult mice by tamoxifen treatment. GsαECKO mice displayed phenotypes of edema, anemia, hypoproteinemia and hyperlipoproteinemia, which indicates impaired microvascular permeability. Mechanistically, Gsα deficiency reduces the level of endothelial plasmalemma vesicle-associated protein (PLVAP). In addition, overexpression of Gsα increased phosphorylation of cAMP response element-binding protein (CREB) as well as the mRNA and protein levels of PLVAP. CREB could bind to the CRE site of PLVAP promoter and regulate its expression. Thus, Gsα might regulate endothelial permeability via cAMP/CREB-mediated PLVAP expression.